The Struggle unto Death (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
This article focuses on the legality of euthanasia and assisted suicide in the Netherlands. Euthanasia and assisted suicide are allowed in certain cases, but there is no consensus with respect to the extent of the situations in which physicians should not be prosecuted. I argue that the individual, and, more specifically, his suffering, should be the focal point, and that the present legislation falls short in this respect; no solution can as yet be offered to individuals whose suffering cannot be resolved through medical means and which cannot be subsumed under the terms the law specifies.
Keywords: Euthanasia; Assisted suicide; Depression; Existential suffering